Effects of “accurate measurement” comprehensive sports activities on balance ability, body composition and bone density of female college students - Zhang, Zhilei; Liu, Jie; Li, Jianguo; Li, Jianping (Frontiers in Physiology, 2023)
Background: A sedentary lifestyle with little movement has affected modern youth, and regular exercise has real benefits for people; such studies are mostly for older adults, and more evidence is needed for adolescents. Objective: To compare differences in balance, body composition, and bone mineral density among female college students before and after an exercise intervention to provide precise evidence that exercise promotes college student health. Methods: A whole group of female students in a university was sampled and included in the statistical analysis 50 people, divided into two cohorts, 21 people in the test group and 29 people in the control group; the test group had 4 comprehensive sports activities per week and the control group had 1 comprehensive sports activities per week, and the differences in each index of balance ability, body composition and bone density before and after the intervention were compared after 3 months. Results:After exercise intervention, when maintaining balance, the area of the center of gravity movement trajectory increased by 32.36% in the test group compared with the pre-intervention period and increased by 42.80% compared with the control group, and the differences were all statistically significant (P < 0.01); body mass index (BMI), body fat rate (BFR), visceral fat area (VFA), skeletal muscle content, and Inbody score increased over time more reasonable, and the difference in the effect of time factor (effect) was statistically significant (P < 0.01); bone mineral density (BMD) and BMD Z value increased with time, and the difference in the effect of time factor was statistically significant (P < 0.05). Conclusion:Female college students' body balance ability improved substantially after exercise intervention; at the university level, female college students had a more rational body composition and continued natural increase in BMD, which were not related to exercise intervention.